The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1161/01.hyp.10.5_pt_2.i52
|View full text |Cite
|
Sign up to set email alerts
|

Ouabainlike Na+,K+-ATPase inhibitor in the plasma of normotensive and hypertensive humans and rats.

Abstract: Acute volume expansion, increased sodium intake, and restraint on sodium excretion endow the plasma with an increased capacity to inhibit sodium transport. Cytochemical techniques can detect the presence of Na+K+-adenosine triphosphatase (ATPase) inhibitor in the plasma of normal humans and rats, the concentration of which is controlled by salt intake. The substance responsible appears to originate in the hypothalamus, where the concentration is also controlled by salt intake. The plasma concentration of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…In the therapy of chronic reversible obstructive airways disease in which allergic inflammation and bronchial hyperresponsiveness are significant pathophysiological factors there are useful drugs that can prevent the late asthmatic reaction and reduce bronchial hyperreactivity. Mazzoni et al 6 showed that asthmaprophylactic drugs such as disodium cromoglycate, ketotifen or hydrocortisone reduce platelet-activating factor (PAF)-induced bronchial hyperreactivity to bombesin or histamine. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the therapy of chronic reversible obstructive airways disease in which allergic inflammation and bronchial hyperresponsiveness are significant pathophysiological factors there are useful drugs that can prevent the late asthmatic reaction and reduce bronchial hyperreactivity. Mazzoni et al 6 showed that asthmaprophylactic drugs such as disodium cromoglycate, ketotifen or hydrocortisone reduce platelet-activating factor (PAF)-induced bronchial hyperreactivity to bombesin or histamine. …”
Section: Methodsmentioning
confidence: 99%
“…Although the chemical nature and the production site of EDF remain to be elucidated, EDF, supposed to be a circulating natural ligand for the cardiac glycoside receptor of Na +,K +-ATPase, could play an important role in the regulation of sodium excretion and may be related to the pathogenesis of hypertension in humans and animals [3][4][5][6]. Because of the lack of specific assay methods, a variety of different procedures have been employed to monitor digitalis-like activity.…”
Section: Inhibitormentioning
confidence: 99%
“…79 This is not in accordance with the working hypothesis that endogenous digitalis is released and causes natriuresis to restore the sodium balance in response to excessive sodium accumulation. 80 Molecules considered to act as EDLFs show exclusively hypertensive effects, 81, 82 but the underlying mechanisms of action seems complex. For example, nanomolar levels of ouabain increase the synthesis and release of angiotensin II (Ang II) from the endothelium of the tail vascular beds of spontaneously hypertensive rats, 83 but also increase nitric oxide release from endothelial cells.…”
Section: The Role Of Endogenous Digitalis In Hypertensionmentioning
confidence: 99%
“…116 Of the bufadienolides, MBG has been studied most extensively. 117, 118, 119, 120 MBG has great affinity for and inhibits the activity of the α 1 -subunit of the Na + ,K + -ATPase, 80 which is the main Na + pump isoform in vascular sarcolemma and renal tubules.…”
Section: The Role Of Endogenous Digitalis In Hypertensionmentioning
confidence: 99%
“…In addition to A N P measurements, we have also studied other hormones implicated in the control o f G F R (catecholamines, renin and vasopressin) [18] and in sodium tubular transport (aldosterone, ouabain-displacing factor, O D F). O D F is a physiological inhibitor of sodium transport competing with ouabain for binding the N a +, K +-ATPase [19] for which association has been demonstrated with vol ume regulation [20], To our knowledge there are no pub lished data in the diabetic state concerning this factor.…”
Section: Introductionmentioning
confidence: 99%